Effect of Audit Committee, Institutional Ownership, and Risk Committee on Audit Quality of Public Companies - Rapini, Titi; Suwandi, Suwandi; Putro, Rizki Listyono; Aulia, Triana Zuhrotun; Sudarmanto, Eko (West Science Accounting and Finance, 2025)
This study examines the influence of audit committees, institutional ownership, and risk committees on the quality of audits in public companies. Using a quantitative approach, data were collected from 160 professionals involved in corporate governance through a structured questionnaire using a Likert scale (1–5). The data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS 3). The results show that all three independent variables—audit committee, institutional ownership, and risk committee—have significant and positive effects on audit quality. The audit committee demonstrates the strongest influence, highlighting its critical role in overseeing financial reporting and auditor performance. Institutional ownership enhances external monitoring, while the risk committee contributes through improved risk oversight. These findings underscore the importance of strong governance structures in ensuring high audit quality and financial transparency in public companies.